HI/DMSO-Based Chemoselective Oxidative Halogenation of Pyrrolo[2,1-a]isoquinolines - Cui, Hai-Lei (Synlett, 2025)
The application of HI in DMSO-based modifications of pyrrolo[2,1-a]isoquinoline derivatives has been explored. Selective chlorinations and iodinations of pyrrolo[2,1-a]isoquinolines have been achieved by using a HI/DMSO-based reaction system. A chlorination/aromatization cascade can be achieved by performing the reaction at 150 °C with NiCl2 as a chlorine source, whereas an iodination product was obtained by carrying out the reaction in PhCl/DMSO with HI at a lower temperature. Furthermore, it was found that the chemoselectivity can be tuned by the use of various additives, thereby providing methylthiolated or formylated pyrrolo[2,1-a]isoquinoline derivatives in acceptable yields.
Keywords: chlorination; dimethyl sulfoxide; hydrogen iodide; iodination; pyrroloisoquinolines